On the Folklore of Old Believers in the Baltic States: Its Origin, Development and Peculiarities - Александрович Новиков, Юрий (Slavistica Vilnensis, 2009)
A comparison of folklore collected from the Old Believers living in the Baltic States reveals a relationship of all traditions and their connections to the folk culture of the Pskov region. A wide repertoire of folk tales, religious songs, Christian legends, charms, series of mythological legends and the peculiarities of their everyday and religious etiquette make this relationship evident. However, the survival tales of the ancestral spiritual heritage are different. Folktales, among them tales of magic, legends about witches and “walking” dead people, cursed treasures, Easter songs, and the ritual of kidnapping brides are mostly preserved in Lithuania. Songs of the yearly cycle as well as wedding songs, certain types of charms and mythological legends are better known in Latvia. Rituals and customs related to the yearly cycle of feasts and the fishing profession are preserved best in Estonia. Historical stories are told very seldom, yet true events are depicted in a mythological way. The author argues that the influence of Lithuanian folklore rather than the influence of Latvian or Estonian folklore is stronger in the texts of Old Believers.